Concurrent depression and anxiety in women undergoing additional diagnostic procedures due to positive screening for cervical cancer - Irena Ilic; Goran Babic; Sandra Sipetic Grujicic; Ivana Zivanovic Macuzic; Milena Ilic; Ana Ravic-Nikolic; Vesna Milicic (PLoS ONE, 2026)
Introduction Undergoing additional diagnostic procedures due to a positive cervical cancer screening in women can lead to psychosocial burden. This study investigated the co-occurrence of depression and anxiety in women both before and after additional diagnostic procedures for cervical cancer. Methods This prospective observational study with repeated measures was conducted in a cohort consisting of all consecutive women (N = 172) who received an abnormal Pap screening test result and therefore presented to a gynecologist for additional diagnostic examinations. Multivariate logistic regression was used to identify the independent predictors of the concurrent depression and anxiety occurrence among women while undergoing additional diagnostic procedures due to positive screening for cervical cancer. Results The prevalence of concurrent depression/anxiety among women while undergoing additional diagnostic procedures due to positive screening for cervical cancer was elevated from 34.3% before diagnostics to 46.5% after diagnostics (P < 0.05). Also, the prevalence of more severe concurrent depression/anxiety was higher after diagnostics than before diagnostics. Multivariate logistic regression presented that worry (regarding cervical cancer, general health, the result of the next cytology test, and having sex) was an independent significant predictive factor for concurrent depression/anxiety in women before undergoing additional diagnostic procedures due to positive screening for cervical cancer. Multivariate logistic regression presented that urban place of residence, history of induced abortion, and sedative use were predictive factors for concurrent depression and anxiety in women after undergoing additional diagnostic procedures due to positive screening for cervical cancer. Conclusion Concurrent depression and anxiety occurrence was highly prevalent among women while undergoing additional diagnostic procedures due to positive screening for cervical cancer. This prospective observational study showed a correlation between certain risk factors and concurrent depression/anxiety, although it is difficult to determine causality of this association due to the limitations of the study design. Only evidence that establishes causality can definitively guide the implementation of specific procedures and interventions during cervical cancer screening aimed at reducing concurrent depression/anxiety.